GROWTH RESPONSE OF SOYBEAN ( Glycine max (L) TO NPK FERTILIZER AND BIO FERTILIZER - Fenty Maimunah Simbolon; Muhammad Rizwan; Noverina Chaniago; Surya Agus Efendy (PT Inovasi Pratama Internasional, 2020)
This research was carried out at the Experimental Garden of the Faculty of Agriculture, Islamic University of North Sumatra, Jln. Eka Warni, Medan Johor District, Medan Municipality with a height of ± 25 meters above sea level with flat topography. The aim of the research was to determine the effect of providing biological fertilizer by reducing the dose of NPK fertilizer on the growth of soybean plants. This research used the Factorial Randomized Block Design (RAK) method with two factors studied, namely: The first factor is bio quality (H) biological fertilizer which consists of 2 treatment levels, namely H 0 (Control), H 1 (10 cc/l water); The second factor is NPK fertilizer with 4 treatment levels, namely N 0 (Control), N 1 (20 g/plot), N 2 (40 g/plot) and N 3 (60 g/plot). The parameters observed were plant height, number of branches per plant, number of root nodules. The results of the research showed that the application of biological fertilizer had a significant effect on the growth of soybean plants, namely the number of branches per plant, but had no significant effect on plant height and number of root nodules. Applying NPK fertilizer has a significant effect on plant height, but does not have a significant effect on the number of branches per plant and the number of root nodules. Meanwhile, the interaction between biological fertilizer and NPK fertilizer had no significant effect on plant height, number of branches per plant, or number of root nodules.